Language alternation in the “closing presentation” of life insurance sales talk - Ishak, Wan Irham; Rafik-Galea, Shameem; Chan, Mei Yuit (Malaysian Association of Modern Languages, 2012)
Sales talk is recognisable as a type of goal-oriented interaction with its specific structure, set of roles, and patterns of language use. In a multilingual society, sales talk between the sales person and the customer often displays alternation of languages by either party as the conversation proceeds. This study examined language choice and code-switching also known as language alternation, as communication resources in the sales talk by life insurance agents when talking to their clients, during the stage known as the “closing presentation”. Through a self-report questionnaire, a follow-up interview, and a recorded conversation between an agent and a client, insurance agents’ preferences regarding the language(s) they use in the closing presentation stage of the sales talk and the reasons why the language(s) are preferred were examined. The findings show that the life insurance agents’ choice of language is dependent on factors such as the language used by the client, the specific insurance product being presented, and the perceived background of the client. Furthermore, examination of the actual conversation between an agent and a client found language alternation being used by agents for both building rapport and distancing, and signalling change in footing.